2006
DOI: 10.1007/s10228-005-0323-1
|View full text |Cite
|
Sign up to set email alerts
|

Responses of immature male masu salmon parr to the urine of mature males

Abstract: Responses of male masu salmon Oncorhynchus masou parr to mature male urine were investigated in a Y-maze trough. Immature masu salmon made fewer entries into the channel conditioned by mature male urine than that with control water. This phenomenon may suggest that immature males avoid sexually active males in the spawning season

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In male tilapia, androgen levels (11KT) are good predictors of dominance [ 19 ], but their effect in urinary tract physiology or urination behaviour is not known. Mature masu salmon show morphological changes in the urinary tract suggesting a functional transition in the kidney related to the release of sex pheromones in both sexes [ 40 , 41 ]. Further investigation is necessary to determine which physiological mechanisms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In male tilapia, androgen levels (11KT) are good predictors of dominance [ 19 ], but their effect in urinary tract physiology or urination behaviour is not known. Mature masu salmon show morphological changes in the urinary tract suggesting a functional transition in the kidney related to the release of sex pheromones in both sexes [ 40 , 41 ]. Further investigation is necessary to determine which physiological mechanisms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The present results indicated that UFR and KSI increased in both sexes at mature stages. These increases may occur because not only mature females, but also mature males, release chemical signals in the spawning season 16 . An advantage of increased urine in spawning season will be effective diffusion for transmitting pheromone signals in both females and males, although the biological functions of pheromones are distinct between females and males.…”
Section: Discussionmentioning
confidence: 99%
“…These increases may occur because not only mature females, but also mature males, release chemical signals in the spawning season. 16 An advantage of increased urine in spawning season will be effective diffusion for transmitting pheromone signals in both females and males, although the biological functions of pheromones are distinct between females and males. It is suggested that in masu salmon the kidney acts as a pool for chemical signals and the urine is effectively released in spawning season.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations